Evidence of Browning of White Adipocytes in Poorly Survived Fat Grafts in Patients. (7th April 2021) - Liu, Tong; Fu, Su; Wang, Qian; Cheng, Hao; Mu, Dali; Luan, Jie
Abstract: Background: Browning adipocytes induced by burn and cancer were assumed less viable and more prone to necrosis for their hypermetabolic properties. Recent studies have shown browning of white adipose after fat engraftment in mice. Objectives: The authors sought to evaluate whether fat transfer could induce browning biogenesis in fat grafts in humans and if it is associated with graft necrosis. Methods: Necrotic adipose grafts were excised from 11 patients diagnosed with fat necrosis after fat grafting or flap transfer. Non-necrotic fat grafts were from 5 patients who underwent revisionary surgeries after flap transfer. Histology and electronic microscopy as well as protein and gene expression of browning-related marker analyses were performed. Results: Fat grafts with necrosis demonstrated a higher gene expression level of uncoupling protein-1 (greater than fivefold increase, ** P  < 0.01), a master beige adipocyte marker, than non-necrotic fat grafts. Electronic microscopy and histology showed that browning adipocytes were presented in necrotic adipose in patients. Conclusions: Fat transfer induced browning adipocytes in patients and was evident in patients with postgrafting necrosis. Level of Evidence: 5: